UJI PENDAHULUAN EFEK KOMBINASI ANTIJAMUR INFUS DAUN SIRIH (Piper betle L.), KULIT BUAH DELIMA (Punica granatum L.), DAN RIMPANG KUNYIT (Curcuma domestica Val.) TERHADAP JAMUR CANDIDA ALBICANS - Soemiati, Atiek; Elya, Berna (Makara Journal of Science, 2002)
The investigation for antifungal effect of medicinal plants, combination infusion of Piper bettle leaves, Punica granatum Fructus Cortec, Curcuma domestica Rhizome. The tested demartophyta used Candida albicans. This research using dilution method to determine of minimum inhibitory concentration (MIC) and difusion method to determine zone inhibition around of disc. The results of determination of MIC showed that combination infusion Piper bettle leaves with Punica granatum Fructus Cortex against C. albicans respectively, 31,2 mg/ml : 7,8 mg/ml; 15,6 mg/ml : 15,6 mg/ml and 7,8 mg/ml : 31,2 mg/ml. The determination for zone inhibition from 3 concentration of infusion of Piper bettle leaves with 3 concentration of Punica granatum Fructus Cortex with 9 combination against C. albicans showed that combination of two infusion is the larger than the single infusion.